DISRUPTIVE RELIGION AND ETHICAL OPPOSITION: THE FORCE OF MORAL AUTHORITY IN INDONESIA’S DEMOCRATIC CONSOLIDATION - Billahi, Savran; Thaha, Idris; Suryani, Suryani; Fachriza, Mohammad Ezha (JWP (Jurnal Wacana Politik), 2026)
This article argues that democratic consolidation in Indonesia cannot be explained solely through the performance of formal institutions. By foregrounding ethical opposition as a missing variable in dominant consolidation theories, it shows that democracy has also been sustained by a normative infrastructure that legitimizes critique beyond institutional arenas. Based on qualitative historical analysis of Abdurrahman Wahid’s and Ahmad Syafii Maarif’s oppositional practices under the New Order and in the post-Reformasi period, the article finds that moral authority enabled non-institutional opposition to constrain state power, normalize dissent, and protect democratic quality. While both figures articulated a corrective and non-subversive mode of opposition, they operated through different mechanisms: Wahid’s opposition was embedded in organizational networks that generated more direct institutional effects, whereas Syafii Maarif’s opposition worked primarily through discursive and normative interventions shaping the moral boundaries of democratic politics. Using the lens of disruptive religion, the article shows that religion functioned not as a political ideology but as a source of moral legitimacy compatible with democratic stability